Civil Law Perspectives Regarding Marriage Annulment According to the Civil Code - Trisnanda Rielta; Zhafira Maliha; Nayla Aulia Rangkuti; M. Radit Febrianda Hasibuan; Jasni bin Sulong (ISNU Sumatera Utara, 2025)
The civil law perspective on the Civil Code regarding marriage annulment reveals the legal basis in the provisions of marriage annulment. This research uses a normative legal research method, which focuses on the study of legal norms, legal documents, and relevant literature. This article is the basis for a marriage to be annulled if there are defects in fulfilling the documents or violating the provisions that have been set. The legal basis for the annulment of marriage in the Civil Code is to maintain order in the application of marriage in Indonesia. However, often in its application this article conflicts with customary norms that apply in Indonesia. Marrying a child who is not yet of age according to the provisions of the Civil Code is a common occurrence in Indonesia. It is not uncommon for such marriages to be based on coercion from parents, which is contrary to the Marriage Law No. 1/1974 Article 6 paragraph 1. The Civil Code also regulates that marriage must be based on the agreement of both candidates Article 27. The legal basis of this article is to protect the rights not only for husband and wife but also to maintain the legitimacy of children born in the event of an annulment of marriage